Impact of diagnosis-to-treatment waiting time on survival in esophageal cancer patients – A population-based study in The Netherlands. Issue 2 (February 2017) - Visser, E.; van Rossum, P.S.N.; Leeftink, A.G.; Siesling, S.; van Hillegersberg, R.; Ruurda, J.P.
Abstract: Background: The aim of this study was to determine whether the waiting time from diagnosis to treatment with curative intent for esophageal cancer impacts oncologic outcomes. Patients and methods: All patients treated by esophagectomy for esophageal carcinoma in 2005–2013 were identified from the Netherlands Cancer Registry. Patients who underwent multimodality treatment and patients treated with surgery only were analyzed separately. Multivariable logistic regression analyses were performed to evaluate the impact of diagnosis-to-treatment waiting time on pT-status, pN-status, and R0 resection rates. Cox regression was applied to estimate the influence of waiting time on overall survival. Analyses were performed with the original scale and in three categorized groups of waiting time (≤5 weeks, 5–8 weeks, and >8 weeks) based on guidelines and previous studies. Results: Of 3839 patients, 2589 underwent multimodality treatment and 1250 were treated with surgery only. In both groups, pT-status, pN-status, and R0 resection rates were not significantly influenced by waiting time ( p -values >0.05). Also, waiting time was not significantly associated with overall survival in the multimodality treatment group (5–8 weeks vs. ≤5 weeks, hazard ratio [HR] 1.12, p = 0.171; and >8 weeks vs. ≤5 weeks, HR 1.21, p = 0.167), nor in the surgery only group (5–8 weeks vs. ≤5 weeks, HR 0.92, p = 0.432; and >8 weeks vs. ≤5 weeks, HR 1.00, p = 0.973). Conclusion: This large population-based cohort study demonstrates that longer waiting time from diagnosis to treatment in patients treated for esophageal cancer with curative intent does not negatively impact pT-status, pN-status, R0 resection rates, and overall survival.